Analgesic Effect of the Neuropeptide Cortistatin in Murine Models of Arthritic Inflammatory Pain. Issue 5 (23rd April 2013) - Morell, Maria; Souza‐Moreira, Luciana; Caro, Marta; O'Valle, Francisco; Forte‐Lago, Irene; de Lecea, Luis; Gonzalez‐Rey, Elena; Delgado, Mario
Abstract: Objective: To investigate the role of the antiinflammatory neuropeptide cortistatin in chronic pain evoked by joint inflammation. Methods: Thermal and mechanical hyperalgesia was evoked in mouse knee joints by intraplantar injection of tumor necrosis factor α and intraarticular infusion of Freund's complete adjuvant, and the analgesic effects of cortistatin, administered centrally, peripherally, and systemically, were assessed. In addition, the effects of cortistatin on the production of nociceptive peptides and the activation of pain signaling were assayed in dorsal root ganglion cultures and in inflammatory pain models. The role of endogenous cortistatin in pain sensitization and perpetuation of chronic inflammatory states was evaluated in cortistatin‐deficient mice. Finally, the effect of noxious/inflammatory stimuli in the production of cortistatin by the peripheral nociceptive system was assayed in vitro and in vivo. Results: Expression of cortistatin was observed in peptidergic nociceptors of the peripheral nociceptive system, and endogenous cortistatin was found to participate in the tuning of pain sensitization, especially in pathologic inflammatory conditions. Results showed that cortistatin acted both peripherally and centrally to reduce the tactile allodynia and heat hyperalgesia evoked by arthritis and peripheral tissue inflammation in mice, via mechanisms that were independent of its antiinflammatory action. These mechanisms involved direct action on nociceptive neurons and regulation of central sensitization. The analgesic effects of cortistatin in murine arthritic pain were linked to binding of the neuropeptide to somatostatin and ghrelin receptors, activation of the G protein subunit Gαi, impairment of ERK signaling, and decreased production of calcitonin gene‐related peptide in primary nociceptors. Conclusion: These findings indicate that cortistatin is an antiinflammatory factor with potent analgesic effects that may offer a new approach to pain therapy in pathologic inflammatory states, including osteoarthritis and rheumatoid arthritis.